Where Do International Students Work after Graduation? Optional Practical Training and the New Geography of Jobs. Issue 3 (3rd July 2022) - Kaemmerer, James; Foulkes, Matt
Abstract : This article examines the geographic distribution of Optional Practical Training (OPT) employment by international student graduates of Missouri's colleges and universities between 2007 and 2017. OPT is a temporary employment program that international students are eligible to apply for after graduating with a degree from a college or university in the United States. It offers twelve months of employment authorization, and students can work anywhere in the United States provided the work is related to their degree. OPT has seen remarkable growth over the past two decades, but employment has mainly concentrated in major urban centers. Based on more than 24, 000 OPT employment addresses of Missouri graduates, this research shows that nearly 97 percent of Missouri's OPT took place in metropolitan areas, most of which was out of state. Within Missouri, OPT employment was regional, with Missouri's OPT students more likely to cross the country to work than to cross the state. Most local OPT work in college towns was located on campuses, rather than in the surrounding community. Indeed, the data show how Missouri's smaller cities, towns, and rural areas—and their local economies—have all but missed out on the benefits of homegrown OPT employment.